2022
DOI: 10.1139/cjz-2021-0082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hunting pressure and timing of harvest on bighorn sheep (Ovis canadensis) horn size

Abstract: Trophy hunting can affect weapon size of wild animals through both demographic and evolutionary changes. In bighorn sheep (Ovis canadensis Shaw, 1804), intense harvest of young males with fast-growing horns may have partly driven long-term decreases in horn size. These selective effects could be dampened if migrants from protected areas, not subject to artificial selection, survived and reproduced within hunted populations. Bighorn rams undertake long-distance breeding migrations in the weeks preceding the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Breeding migration partially removes the protection that National Parks and other protected areas provide to populations within their boundaries. We modelled migration probability based on local conditions, notably the level of competition among males and the adult sex ratio (Lassis et al, 2022b ). However, bighorn males also conduct prospective trips in October–November to assess their breeding potential in other populations (Lassis et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breeding migration partially removes the protection that National Parks and other protected areas provide to populations within their boundaries. We modelled migration probability based on local conditions, notably the level of competition among males and the adult sex ratio (Lassis et al, 2022b ). However, bighorn males also conduct prospective trips in October–November to assess their breeding potential in other populations (Lassis et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…High hunting pressure, by reducing the number of large and competitive males, may increase the incentive of males to migrate from protected to harvested areas (Hogg, 2000 ). As local horn length declines, an increasing proportion of males would not be sampled through the legal hunt because they do not fit the legal definition of minimum curl (Pelletier et al, 2012 ), and an unknown but likely increasing proportion of migrants from neighboring parks would be shot (Lassis et al, 2022b ; Pelletier et al, 2014 ; Poisson et al, 2020 ), reducing the reliability of harvest data to monitor local temporal trends in horn size (Festa‐Bianchet et al, 2015 ; Leclerc et al, 2016 ; Pelletier et al, 2012 ). Notably, we found that at high harvest rate, an increasing proportion of the harvest is made up of males originating from protected areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, we propose that the combination of slot size limits with strategically placed MPAs in a network would be a strong synergy, which should increase the proportion of large lobsters with fast-growing phenotypes outside MPAs as they would be protected when moving out. Emigration from protected areas can provide phenotypic rescue to areas where individuals with large body size or other key traits have become rare due to harvesting [ 28 , 32 , 75 , 76 ]. Surrounding areas may also receive a higher influx of larvae that carry fast-growth genotypes, and in that way contribute to a genotypic rescue that buffers evolutionary changes in growth rates.…”
Section: Discussionmentioning
confidence: 99%